2019
DOI: 10.1007/s40090-019-0188-1
|View full text |Cite
|
Sign up to set email alerts
|

The application of thermally activated persulfate for degradation of Acid Blue 92 in aqueous solution

Abstract: Thermally activated persulfate (TAP) was applied for the degradation of Acid Blue 92 (AB92) dye in its aqueous solution. The effects of pH (3-11), temperature (298-333 K), contact time (15-75 min), sodium persulfate (SPS) concentration (0.05-0.5 mM) and initial AB92 concentration (50-400 mg/L) on the degradation of AB92 using TAP were examined. The initial and residual AB92 concentrations were determined spectrophotometrically at the wavelength of 260 nm and the dye mineralization was examined via the total or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 86 publications
3
18
0
Order By: Relevance
“…A recent report suggested that the degradation efficiency of acid orange G (AOG) decreased with increased AOG concentration when activating peroxymonosulfate using a Co-Mn-layered double hydroxide [33]. It was also found that the degradation performance of Acid Blue 92 was inhibited at higher dye concentrations when using the thermally activated persulfate process [34].…”
Section: Effect Of Rhb Concentrationmentioning
confidence: 99%
“…A recent report suggested that the degradation efficiency of acid orange G (AOG) decreased with increased AOG concentration when activating peroxymonosulfate using a Co-Mn-layered double hydroxide [33]. It was also found that the degradation performance of Acid Blue 92 was inhibited at higher dye concentrations when using the thermally activated persulfate process [34].…”
Section: Effect Of Rhb Concentrationmentioning
confidence: 99%
“…Several treatment methods have been proposed for the removal of dyes from contaminated waters which include photodecomposition, electrolysis, adsorption, oxidation, biodegradation and coagulation–flocculation [[7], [8], [9], [10], [11], [12]]. Amongst the different physical and chemical treatment processes, adsorption is an effective technique which is successfully used for the removal of colors from wastewaters [7].…”
Section: Description Of Protocolmentioning
confidence: 99%
“…Although during these two reactions, the hydroxyl radical is produced but the presence of sulfate anion as a radical scavenger results in decrease of hydroxyl or sulfate radical activity. Studies were showed that process efficiency were decreased with increasing the pH of solution 21,22 …”
Section: Resultsmentioning
confidence: 99%
“…So, this study was followed the pseudo‐first‐order kinetic model. Previous study, 20,22,26,43 were reported that treatment of textile wastewater followed the pseudo‐first‐order kinetics.…”
Section: Resultsmentioning
confidence: 99%